(3MGTjI Ydi TQM HGfJ SYGO dCHf gTGe GdCfUGQjs - (3YHO GdbGOQ Hf YeQ GdHZOGOj , J (B1093 (3g` s; (3YHO Gddg Hf jhSa Hf CMeO Hf YHO Gddg Hf jhSa , GHf gTGe , LeGd GdOjf , CHh eMeO,J (B761 (3g` s ((3eMeO CHj GdfUQ Hf jhSa Hf CSYO Hf YHOGddg Hf gGTe GdLYaQj GdfGHdSj s)
(3ChdgG (B:s
(3MeOG def cSG NhGU YHGOg HQOI GdeOGFM hGdeMGeO hfTQ Mdd GdKfGA Ydi YhGWa GdCcGQe GdCeGLO s
(3BNQgG (B:s
(3hPcQg CjVkG aj ehGVY HYOg hgPG BNQ eG CQOfG EjVGMg LYdg Gddg NGdUkG dhLgg GdcQje s
(3ocJHJ HQSe GdYdGeI CMeO JjehQ HNW fGSNgG GdPj cJH GdeLdO GdChd SfI (B1333(3g`s
(3hGdKGfj SfI (B1334(3g`s
(3hHgG ebOeI cGedI JNJda Yf ebOeI GdfSNI GdSGHbIs
(3fSNI KGfjIs
(3HChdgG SHYI agGQS s
(3bQf GdfSN (B:s
Keywords: (3GdCOHs